Government control in increasing vehicles taxpayer compliance - Zulkieflimansyah, Zulkieflimansyah; Nurjihadi, Muhammad; Hasri, Diah Anggeraini; Ananda, Nova Adhitya; Hakim , Lukmanul (Technium Social Sciences Journal, 2021)
This study aims to determine the dynamics of taxpayer compliance from time to time by using a mathematical model. This study uses two analysis tools, namely differential equations, to create a model of taxpayer compliance and Moderated Regression Analysis to determine the effect of moderating government control on increasing taxpayer compliance. This study indicates that government control can reduce the number of non-compliant taxpayers by looking at the sensitivity index. The results of the sensitivity index of government control parameters can reduce the basic reproduction number. Statistically, it is also proven that the moderation of government control can strengthen the effect of awareness on taxpayer compliance by 82.5%.